Qard Al-Hasan: the concept of helping in Al-Rahnu financing and its practice in MAIDAM / Salimah Yahaya ... [et al.] - Yahaya, Salimah; Mohd Noor, Nor Adila; Muhammad, Hamizah; Ismail, Che Zuina (Academy of Contemporary Islamic Studies (ACIS), 2022)
Qard al-Hasan is a charitable loan agreement. AlRahnu institutions still practice the Qard al-Hasan contract, but the issue is, not all al-Rahnu institutions apply 100% welfare loans. This article has two research questions; i) how is the concept of helping each other in the matter of debt according to Islam? and ii) how is the concept of Qard al-Hasan applied by al-Rahnu in the Terengganu Council of Islamic Religion and Malay Custom (MAIDAM)? This article adopts secondary data collection methods through document review to obtain relevant information. The findings showed that the loan through the Qard al-Hasan contract could not generate any profit as it is a voluntarily process on the basis of helping. Al-Rahnu MAIDAM uses the Qard al-Hasan contract and does not deviate from the Islamic path. Although al-Rahnu MAIDAM operates at a small profit, the Qard al-Hasan contract is still applied for charitable purposes, which is to help the community to obtain cash by taking only a small amount of fee charge for safekeeping.